2020
DOI: 10.1177/1356766720952122
|View full text |Cite
|
Sign up to set email alerts
|

Mobile hotel reservations and customer behavior: Channel familiarity and channel type

Abstract: The present study is centered on mobile hotel reservations in the investigation of the interrelationships between value, attitude, satisfaction, and reuse intention in consideration of the moderating roles of the channel familiarity and the channel type. Utilizing a quantitative approach, the research hypotheses were tested using structural equation modeling and multiple-group analyses. The casual relationships proposed among the study variables were found to all be significant, and the importance of the utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…The studies constantly provide evidence that the perceived value toward new technologies aids customers to develop a favorable attitude [39]. Ashfaq [40] examined the perceived values of smart speakers of customers in the US, and their results supported that the functional, hedonic, and economic aspects of perceived value increase the consumers' attitude.…”
Section: Perceived Valuementioning
confidence: 96%
See 2 more Smart Citations
“…The studies constantly provide evidence that the perceived value toward new technologies aids customers to develop a favorable attitude [39]. Ashfaq [40] examined the perceived values of smart speakers of customers in the US, and their results supported that the functional, hedonic, and economic aspects of perceived value increase the consumers' attitude.…”
Section: Perceived Valuementioning
confidence: 96%
“…In the same manner, studies have observed that an individual's attitude is of great importance to form consumer behavior toward technology-based products and services. For example, the significant association between attitude and behavior has been validated with the adoption of information systems [45], mobile applications [39], and robots [46]. For example, Hwang et al [22] examined the relationship between individual attitudes towards innovative technological services and behavioral intentions, and they confirmed a significant link.…”
Section: Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…The tremendous development of wireless communication technology has significantly transformed the global business environment, especially for mobile e-commerce (Lin and Wang, 2006; Nel and Boshoff, 2020). In the hotel industry, the mobile distribution channel accounts for more than one-third of the total hotel bookings, becoming a prevailing e-commerce channel (Hua et al , 2019; Kim et al , 2020). Increasingly hospitality operators have supplemented their online distribution channels with mobile application (app) channels (Wu and Law, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile apps demonstrate significantly different characteristics from computer websites as follows: compared to time on a website (14%), people spend considerably more time on a mobile app (84%; Kumar et al , 2018). Users install various apps on their mobile devices, which implies relationships with brands or channels (Kim et al , 2020). Apps are usually less content-rich and more personalized than websites (Taylor and Levin, 2014).…”
Section: Introductionmentioning
confidence: 99%